Heracles and the Ancient East: Between Similarity and Equivalence - Kechagias, Asterios Evangelos (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
The present research aims to investigate the mythological background of Heracles and his association with some of the main oriental characters towards which he seems to converge. Every character will be examined in its historical context and through several ancient sources, iconography or archaeological material. The aims of this article are threefold: a) to present the connections that occur between Heracles and each of the above figures, showing their similarities and differences; b) to try to find points of spatio-temporal intersection of these characters both with Heracles and with each other; and c) to examine whether, which of these oriental figures and to what extent they can shed light on the ancient biography of this particular hero. The result of the research is that the Greek Heracles is largely an eastern figure and that he was possibly composed from features of Ninurta, Nergal and Melqart, who were found in the eastern Mediterranean shortly before his appearance in Greece, having simultaneously evident links with Indra.